2020
DOI: 10.1371/journal.pone.0227761
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ underestimation of their child’s weight status. Moderating factors and change over time: A cross-sectional study

Abstract: BackgroundParents' underestimation of their child's weight status can hinder active participation in overweight prevention programs. We examined the level of agreement between the parents' perception of their child's weight status and the child's actual weight status, moderating factors, and change over time. MethodsThis cross-sectional study used data collected in 2009 (n = 8105), 2013 (n = 8844) and 2017 (n = 11,022) from a community-based survey conducted among parents of children age 2-12 years in the Neth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 53 publications
(88 reference statements)
2
25
1
1
Order By: Relevance
“…Moreover, among normal weight children the discussions with parents were reported more frequently by children with incorrect underestimation of their weight, while among overweight children the discussion with parents on this issue were more frequent among those who correctly estimated that their weight was too high. Similarly to studies from other countries, these data suggest that if parents fail to correctly estimate the weight of their children, it is unlikely they will recognize the importance of interventions targeting the promotion of healthy nutrition and body weight management [ 5 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Moreover, among normal weight children the discussions with parents were reported more frequently by children with incorrect underestimation of their weight, while among overweight children the discussion with parents on this issue were more frequent among those who correctly estimated that their weight was too high. Similarly to studies from other countries, these data suggest that if parents fail to correctly estimate the weight of their children, it is unlikely they will recognize the importance of interventions targeting the promotion of healthy nutrition and body weight management [ 5 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 71%
“…At the same time, our study showed that 21.1% of the parents did not correctly estimate the weight of their children; again, this situation was more frequent among the parents of overweight children in comparison with those with normal weight. Studies from other studies highlighted that parents’ misperceptions regarding the weight of their children vary depending on country/region, their children’s age group, the actual weight of children and the time when the study was performed, with several studies showing that these misperceptions are more likely among the parents of overweight children [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. For instance, a large study from Australia showed that one quarter of mothers misclassified the weight of their 14 years old children, while a—country European study showed that 27.6% of parents of overweight/obese children underestimated their children’s weight status [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential limitation is the fact that this study enrolled participants based on parental evaluation of their child’s weight status, with most parents being of medium or higher educational level. It has been reported that parents of low educational level tend to underestimate their child’s weight and perceive them as normal weight although they are overweight or obese [ 44 ]. Therefore, results should carefully be generalized to medium to high educational level families.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos indicam que os pais dificilmente identificam corretamente o peso dos filhos (e.g., Chaparro, Langellier, Kim, & Whaley, 2011;Duncan, Hansen, Wang, Yan, & Zhang, 2015;Eckstein et al, 2006;Jones et al, 2011;Oude Luttikhuis, Stolk, & Sauer, 2010;Ruiter et al, 2020;Tompkins, Seablom, & Brock, 2015). Uma meta-análise recente, com crianças e adolescentes entre os 2 e os 18 anos, demonstrou que 1 em cada 7 pais subestimou o peso dos filhos com peso normal e cerca de 50% subestimou o peso dos filhos com excesso de peso e obesidade, sendo esta subestimação maior em crianças entre os 2 e os 5 anos (Lundahl, Kidwell, & Nelson, 2014).…”
Section: Perceções Parentais Sobre O Peso Da Criança Vs Peso Realunclassified